2006
DOI: 10.1021/jf062409z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Carotenoid-Loaded Oil-in-Water Emulsions in Colon Carcinoma Cells in Vitro

Abstract: Oil-in-water emulsions allow the preparation of lipophilic compounds such as carotenoids in the liquid form. Here, the effect of a combination of some emulsifiers, such as two whey protein isolates (BiPro and BioZate), sucrose laurate (L-1695), and polyoxyethylene-20-sorbitan-monolaurate (Tween 20), on the stability of lycopene and astaxanthin in emulsions, droplet size, and cellular uptake of these carotenoids has been investigated. The degradation of lycopene was slightly more pronounced than that of astaxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 24 publications
6
46
0
3
Order By: Relevance
“…The results also showed that, unlike proteins, the incorporation of astaxanthin in polysaccharide stabilizers caused a decrease in their cellular uptake. These findings were also in good agreement with the results reported by Ribeiro et al (2006).…”
Section: Cellular Uptake Of Astaxanthin Colloidal Particlessupporting
confidence: 93%
“…The results also showed that, unlike proteins, the incorporation of astaxanthin in polysaccharide stabilizers caused a decrease in their cellular uptake. These findings were also in good agreement with the results reported by Ribeiro et al (2006).…”
Section: Cellular Uptake Of Astaxanthin Colloidal Particlessupporting
confidence: 93%
“…However, recent advancements in drug delivery have shown that the internalization of therapeutics needs to be augmented also by active transport mechanisms, and therefore not only carrier size and charge, but also elasticity and surface composition are important (Agarwal and Roy, 2013). In this respect, previous literature studies demonstrated that polysorbate 20 exhibits good ability to attach on the membrane of intestinal cells like HT29 cell line with an efficient cell penetration capacity (Ribeiro et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, homogenisation has been used to prepare oil-in-water emulsions or nanoemulsions containing carotenoids, such as lycopene (Boon et al, 2009;Ribeiro, Ax, & Schubert, 2003), lutein (Losso, Khachatryan, Ogawa, Godber, & Shih, 2005) and b-carotene (Chu, Ichikawa, Kanafusa, & Nakajima, 2007Silva et al, 2010). The bioavailability of carotenoids encapsulated within emulsions or nanoemulsions has been reported to be increased when compared to non-encapsulated carotenoids (Grolier, Agoudavi, & Azaisbraesco, 1995;Parker, 1997;Ribeiro et al, 2006), which may enhance their health promoting activities.…”
Section: Introductionmentioning
confidence: 99%